PLN Digital Communication Creativity In Handling Customer Complaints Through The Swacam Feature On The PLN Mobile Application - Puti Kayo Octaviani; Wulan Furrie Lenggana (LPPM Universitas PGRI Sumatera Barat, 2024)
This research aims to analyze and evaluate PLN's digital communication creativity in handling customer complaints through the swacam feature in the PLN Mobile application at PLN UP3 (Customer Service Implementation Unit) Cempaka Putih, the obstacles faced, and efforts to overcome them. This research uses descriptive research with a qualitative approach. Data collection techniques used interviews, observation, and documentation. This research uses Rogers' (2003) theory which includes aspects of Innovation, Communication Channels, Timeframe, and Social System. The results showed that the Swacam feature is an effective digital innovation in improving responsiveness and customer satisfaction. PLN proactively conducts socialization to introduce and attract customers to use this feature. The adoption process of the Swacam feature is still relatively slow because there are still some customers who are less familiar with digitalization. For this reason, PLN UP3 Cempaka Putih coordinates with citizen communities and community leaders to disseminate information and encourage the use of the swacam feature to residents in the surrounding environment.